Effects of virtual exposure to urban greenways on mental health - Jiang, Xiangrong; Wang, Xiaocan; He, Linxin; Gu, Qingrui; Wei, Xin; Xu, Mengfei; Sullivan, William C. (Frontiers in Psychiatry, 2024)
Urban greenways (UGW) are increasingly recognized as vital components of urban green infrastructure (UGI). While existing research has provided empirical evidence on the positive impacts of UGW on physical health, studies focusing on the effects on mental health remain limited. Moreover, previous investigations predominantly compare UGW as a whole with other built environments, neglecting the influence of specific vegetation designs along UGW on mental health. To address this research gap, we conducted a randomized controlled experiment to examine the impact of vegetation design along UGW on stress reduction and attention restoration. A total of 94 participants were randomly assigned to one of four UGW conditions: grassland, shrubs, grassland and trees, or shrubs and trees. Utilizing immersive virtual reality (VR) technology, participants experienced UGW through a 5-min video presentation. We measured participants' subjective and objective stress levels and attentional functioning at three time-points: baseline, pre-video watching, and post-video watching. The experimental procedure lasted approximately 40 minutes. Results of the repeatedmeasures ANOVA revealed that participants experienced increased stress and mental fatigue after the stressor and decreased levels following the UGW intervention. Furthermore, between-group analyses demonstrated that the shrubs group and the grassland and trees group exhibited significantly greater stress reduction than the grassland group. However, there are no significant differences in attention restoration effects between the four groups. In conclusion, virtual exposure to UGW featuring vegetation on both sides positively affected stress reduction and attention restoration.It is recommended that future UGW construction incorporates diverse vegetation designs, including shrubs or trees, instead of solely relying on grassland. More research is needed to explore the combined effects of shrubs and trees on mental health outcomes.